FRI0583-HPR Stair climbing - an insight and comparison between women with and without joint hypermobility. (23rd January 2014) - Luder, G.; Schmid, S.; Müller, C.; Stutz, U.; Stettler, M.; Radlinger, L.
Abstract : Background: Joint hypermobility (JH) is a frequent and important entity in rheumatology, which has not received adequate attention and is still not fully understood. Perceived joint instability, a higher risk for joint distortions and chronic pain are the major problems in affected persons(1 ). Even fibromyalgia, chronic fatigue syndrome or early osteoarthritis were recently associated with JH(2 ). Stair climbing is an important functional task and can lead to pain or joint instability in JH. Especially in stair descent fast stabilization of the joints is important, while the maximal vertical force of about 1.5 times body weight is reached in 150 ms after foot contact in healthy(3 ). However, muscle activation and ground reaction force paaterns during stair climbing in persons with JH remain unknown. Objectives: To explore whether differences exist in the muscle activation and ground reaction forces (GRF) between women with and without JH. Secondary aim was to detect differences between hypermobile women with and without symptoms. Methods: 170 women participated in this cross-sectional study: 67 normomobile (24.8±5.4 years), 56 hypermobile with symptoms (25.3±5.4 y) and 47 hypermobile without symptoms (25.7±5.3 y). Groups were identified using the Beighton Score. Symptoms were recorded monthly for half a year and all women mentioning at one time-point pain or disability were classified as symptomatic. GRF were measured with two force plates embedded in a six step staircase. EMG of six leg muscles was measured with surface electrodes. For GRF first maximum peak was calculated and normalized to body weight. Timing of first peak and total contact time were evaluated(3 ). EMG was normalized to maximum voluntary contraction. The linear envelope (Lowpassfilter at 20 Hz) of six strides was averaged and peak activation was calculated, as well as the activation level at first force peak(4 ). Group comparisons were done by oneway ANOVA and post-hoc with Tukey-test, at a significance level p≤0.05. Results: Groups did not differ in age, weight and height. For GRF parameters no significant difference was found between the groups. For stair ascent the EMG measurements showed significant lower activation levels for vastus medialis in both hypermobile groups and no difference in all other muscles. During descent only the semitendinosus muscle had significantly lower maximal activation in both hypermobile groups. Conclusions: GRF revealed no differences between groups and in the EMG measurements only two muscles showed differences. This may indicate that the JH of these women did not affect their ability to negotiate stairs. Furthermore it made no difference whether the women had pain or disability in daily life. A possible explanation is that the women in this study had mild to moderate symptoms and not all of them reported their problems in the lower extremity joints. Finally stair climbing might have not been challenging enough for these rather young persons to show possible differences in movement control. More difficult tasks, such as running or jumping might reveal differences between women with and without JH and also provoke more symptoms in the hypermobile persons. References: Simmonds & Keer. Manual Therapy 2007;12:298-309. Castori et al. Am J Med Genet A, 2012;158A:2055-2070. Stacoff et al. Gait Posture 2005;21:24-38. Frigo & Crenna. Clinical Biomechanics 2009;24:236-245 Acknowledgements: The study was supported by the Swiss National Science Foundation (# 13DPD6 127285) and approved by the local Ethics Committee (# 229/2008). Disclosure of Interest: None Declared